(untitled) (Journal of the Management Sciences, 2024)
The new wave of campus dating in Nigeria Tertiary institutions and its disruptive effect on academic activities is quite alarming. This is largely due to the influence of social media and the development of many different apps and web sites. In order to fully understand the magnanimity of this on academic performance of students, the paper, through literature review and analysis of three related theories, explored the causes of campus dating which include, peer group influences, coercive parental training, and permissive society. It is also caused by the desire to belong and desire for sex, adventures and exploration as well as social and economic reasons. The papers discovered that some of the romantic activities happen during school hours, and this make the dating partners to loose focus and interest in their academic work. The paper also opined that campus dating also has many health related and educational implications. This including dropping of out of school due to unwanted pregnancy as well as the contaminations of various sexual transmitted diseases. The paper finally recommends that parents should devote more attention to training their children and monitoring the type of internet facilities and friends they interact with in the school and at home. Tertiary Institutions should control the dressing mode and other romantic activities, especially cohabitation of their students. The Government should sensor the types of films and movies displayed in this country.